2021
DOI: 10.1088/1361-6463/abd6d3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and size-dependent photoluminescence in colloidal CdTe and Cd x Zn1−x Te quantum dots

Abstract: Semiconductor colloidal quantum dots (QDs) of CdTe and alloyed Cd x Zn1−x Te QDs with N-acetyl-L-cysteine capping ligands are synthesized by a reflux method in aqueous solution. Alloying provides a new degree of freedom to tune the optical and electronic properties of the nanocrystals. The photoluminescence (PL) of Cd x Zn1−x Te QDs is sharper and displays a highly enhanced quantum yield (QY) of 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The position of diffraction peaks at wider angle indicates the alloy effect. Balakrishanan et al and Qian et al also observed broadened and less intense CdZnTe diffraction peaks in their reports[2,11]…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The position of diffraction peaks at wider angle indicates the alloy effect. Balakrishanan et al and Qian et al also observed broadened and less intense CdZnTe diffraction peaks in their reports[2,11]…”
mentioning
confidence: 83%
“…To this mixture, required quantities of sodium tellurite and reducing agent NaBH 4 are added as per the molar ratios and maintained a high stirring rate. When the solution began to show slight color changes a reaction temperature of 100 0 C provided for a time period of 7 hours to form the Cd 0.7 Zn 0.3 Te alloy quantum dots [1,2,7,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fitting Eopt data for CdTe quantum dots to the O'Donnell and Chen model showed that decreasing particle sizes from 3.6 nm to 2.6 nm caused an increase in S from 1.9 to 2.4 and an increase in áħwñ from 12.3 meV to 12.7 meV. 34 This phenomenon has been widely observed for quantum dots and has been attributed to enhanced exciton-phonon interactions in smaller crystallite sizes. 35 Furthermore, theoretical analysis predicts S to be proportional to a 3 /V, where a represents the Bohr radius and V the particle volume.…”
Section: Mil-125mentioning
confidence: 96%
“…16 Balakrishnan et al synthesized CdZnTe QDs in aqueous solution by a reflux method. 17 Compared to CdTe QDs, CdZnTe QDs have less nonradiative recombination centers and lower defect density. Some studies have been reported the synthesis of Mn 2+ partially substituted Cd 2+ ions in CdTe lattices.…”
Section: Introductionmentioning
confidence: 99%